How Islamic Tradition Benefits Nature and Climate Change Action - Mangunjaya, Fachruddin M. (The Journal of the Siam Society, 2023)
This paper explores the contribution of Islamic tradition and teachings in Southeast Asia, particularly in Indonesia, to benefit nature and climate change action. Indonesian Muslims follow the idea of Islamic jurisprudence (fiqh) based on the Imam Syafi’i school of thought, whose principles are practiced in daily life and provide many positive teachings on nature as God’s creation. Humans are regarded as the khilafah fil al ard, stewards of the earth, and the Qur’an teaches that God has created everything in the heavens and on earth as ayat, the sign of God. In Indonesia, organizations and scholars have explored the potential of Islamic teachings for climate action in the form of fatwas (verdicts) and for awakening the people’s awareness of climate change through religious lectures. Government officials and green activists have worked in partnership with the Ulama Council of Indonesia, Muslim leaders, and communities to issue important fatwas on certain issues including forest burning and the protection of wildlife. The Islamic principles of charity and finance, such as zakat, infaq, shadaqah and waqf as well as green sukuk (Islamic bonds), are also beginning to be mobilized for climate change action, including forest conservation. A Sumatra tradition of lubuk larangan has been applied to managing river environments. These examples show the potential of Islamic teaching to promote values important for combatting the climate crisis.